2016
DOI: 10.1017/jfm.2016.778
|View full text |Cite
|
Sign up to set email alerts
|

Linear instability of low Reynolds number massively separated flow around three NACA airfoils

Abstract: Two- and three-dimensional modal and non-modal instability mechanisms of steady spanwise-homogeneous laminar separated flow over airfoil profiles, placed at large angles of attack against the oncoming flow, have been investigated using global linear stability theory. Three NACA profiles of distinct thickness and camber were considered in order to assess geometry effects on the laminar–turbulent transition paths discussed. At the conditions investigated, large-scale steady separation occurs, such that Tollmien–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
58
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 56 publications
9
58
1
Order By: Relevance
“…Three-dimensional short-wavelength instability mode determined from global stability analysis for a NACA 4415 airfoil at Re = 500 and α = 20 • . (a) Streamwise vorticity (ω ζ ) isosurface of the short-wavelength eigenmode and (b) the corresponding wall-streamlines, superposed upon the time-periodic base state[169]. Reprinted with permission from Cambridge University Press.…”
mentioning
confidence: 99%
“…Three-dimensional short-wavelength instability mode determined from global stability analysis for a NACA 4415 airfoil at Re = 500 and α = 20 • . (a) Streamwise vorticity (ω ζ ) isosurface of the short-wavelength eigenmode and (b) the corresponding wall-streamlines, superposed upon the time-periodic base state[169]. Reprinted with permission from Cambridge University Press.…”
mentioning
confidence: 99%
“…For example, by combining local and global linear stability analyses on the flow around airfoils at a low angle of attack, Theofilis et al [20] and Lin and Pauley [21] were able to attribute the dominant perturbation to the Kelvin-Helmholtz (KH) mode. Likewise, at a high angle of attack, a similar dominance by the KH mode was found in the massively separated flow around a series of NACA airfoils at a low Reynolds number [22,23]. For steady separated flow around an airfoil at a low Reynolds number, Kitsios et al [24] observed the existence of three-dimensional stationary modes, which were first reported by Theofilis et al [25] in a flat-plate boundary layer.…”
mentioning
confidence: 52%
“…For example, earlier studies found a growing stationary mode (in a three-dimensional setup), which dominates the decaying wake mode. Detailed analysis performed later clarified the observations [44] . The problem highlights the importance of the a priori known shift value in Arnoldi-based techniques.…”
Section: Naca0015 Airfoil At Stalled Conditions (Naca2d)mentioning
confidence: 96%
“…Results from both matrix-forming as well as time-stepper approaches [42,43,41,44] are available for comparison, albeit in an incompressible framework. While earlier studies [42,43] have used a BiGlobal code with conformally mapped curvilinear co-ordinates to obtain eigenmodes, subsequent studies [41,44] use open-source codes, including Nektar++ and Nek5000 for the time-stepper approach, and FreeFEM++ for matrix-forming. In these studies, the Arnoldi subspace iteration is used for the relevant eigenspectrum computation, with the goal of identifying the smallest modulus modes.…”
Section: Naca0015 Airfoil At Stalled Conditions (Naca2d)mentioning
confidence: 99%